Retrograde aortic valve crossing of the corevalve prosthesis using the buddy balloon technique. Issue 6 (24th October 2013) - Noble, Stephane; Roffi, Marco
<x xml:space="preserve">Abstract</x> In rare cases, retrograde aortic valve crossing during transcatheter aortic valve implantation may be challenging despite improvements in delivery catheter profile, size, and steerability compared with the first generation devices. Herein, we report a case of challenging transfemoral Medtronic CoreValve placement that was possible, thanks to the buddy balloon technique, using a peripheral 6‐F compatible balloon. © 2013 Wiley Periodicals, Inc.